A pilot study adapting and validating the Harvard Trauma Questionnaire (HTQ) and PTSD checklist-5 (PCL-5) with Indian women from slums reporting gender-based violence - Anushka R. Patel; Elana Newman; Julia Richardson (BMC, 2022)
Abstract Background Despite high rates of gender-based violence (GBV) in India, culturally sensitive measures that examine universal and culturally relevant trauma reactions are lacking. Although the Harvard Trauma Questionnaire (HTQ) has been used in India, no study has adapted the measure in full for use with this population. Similarly, the  PTSD checklist-5 (PCL-5) has not yet been validated in India. This study describes the adaptation, validation, and results from the adapted HTQ, and embedded PCL-5, for Indian women from slums reporting GBV. Method This study used the adaptation framework proposed by the HTQ measure developers. The adapted HTQ contained a (1) trauma screen relevant for stressors faced by Indian women from slums, (2) description of the index trauma, (3) description of any ongoing stressors, (4) universal trauma reactions (i.e., PTSD measured by the PCL-5), and culturally relevant trauma reactions (i.e., idioms of distress measured by a scale developed for the study). This measure was piloted on 111 women from Indian slums in face-to-face interviews. Trauma characteristics, types of ongoing stressors, and psychometric properties of the PCL-5 and idioms of distress scale were explored. These scales were validated against measures of depression (PHQ-9), anxiety (GAD-7), and somatic complaints (PHQ-15). Results The majority of participants (77%) reported physical beatings, 18% reported unwanted sexual touch, and 28.8% reported infidelity as the primary emotional abuse. Further, 96.7% of GBV was perpetrated by partner or family member and over half reported ongoing stressors (e.g., poverty-related strain). The PCL-5 embedded in the HTQ yielded good internal consistency (Cronbach's alpha = .88) as did the idioms of distress scale with deletion of one item (Cronbach's alpha = .80). Both scales were externally valid, yielding large correlations with depression, anxiety, and somatic complaints (rs between .54 and .80, ps < .05). Discussion This is the first study to develop a comprehensive measure of trauma exposure with universal and culturally relevant trauma reactions in India. This study also enhances HTQ usage in India by delineating all the steps in the adaptation process. Results can inform the development of trauma-focused interventions for Indian women from slums.